Value4Her: Boosting women-led agribusiness - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
Women are key players in agriculture, but few are engaged in agribusiness. This is largely because women face challenges that bar their entry to this lucrative sector, including poor access to markets, market intelligence, finance and other business services, and because they commonly lack the technical, management and leadership skills needed to drive an enterprise forward. VALUE4HER: Strengthening women’s agribusiness enterprises in ACP countries is set to change this.